Molecular identification and genetic diversity among Photorhabdus and Xenorhabdus isolates - Moghaieb, Reda E. A. (3 Biotech, 2017)
Five bacterial strains were isolated from the hemocoel of the greater wax moth larvae (Galleria mellonella) infected with the entomopathogenic nematodes: Heterorhabditis bacteriophora HP88, Heterorhabditis indicus RM1 and Heterorhabditis sp (S1), Steinernema abbasi and Steinernema sp. (S II). Strains were identified as Photorhabdus luminescens HRM1, P. luminescens HS1, P. luminescens HP88, Xenorhabdus indica and X. nematophila ATTC19061 using 16S rDNA sequence analysis. To reveal the genetic diversity among these strains, three molecular markers (RAPD, ISSR and SRAP) were employed. RAPD analysis showed 73.8 and 54.5 polymorphism percentages for the Photorhabdus and Xenorhabdus strains, respectively. ISSR analysis resulted in 70.1 and 75.2 polymorphism percentages among the Photorhabdus and Xenorhabdus strains, respectively. The SRAP analysis indicated that 75.6 and 61.2% genetic polymorphism was detected among Photorhabdus and Xenorhabdus strains, respectively. The cluster analysis grouped the three Photorhabdus strains together in one cluster and the two Xenorhabdus strains together in another cluster indicating the phylogenetic relationships among them. The genotype-specific markers detected from the three molecular markers (RAPD, ISSR and SRAP) were sufficient to distinguish between the different bacterial strains tested and can be used in the future IBM program that could be built on the use of these strains.